A Comprehensive Study of Radial Load Fluctuation on Alloy Wheels for Electric Vehicles - Dinesh Burande; Ravikant Nanwatkar (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
Electric Vehicle’s alloy wheels are designed to allow for better heat dissipation. Manufacturers carry out many tests of a wheel to be sure, that the wheel will fit for safety reason as also their comfortability level is even bigger. Therefore, a specific design was selected for which the simulations of alloy wheel were performed under real loading conditions. The main objective of this research is to analyze the effects of radial load fluctuations on alloy wheels in passenger car. Radial loads place high stress on alloy wheels when the vehicle is running and affects their life, so that it has excellent performance. This is important to increase the quality and reliability levels of wheel design, durability standards in automotive engineering. Utilizing advanced fatigue analysis methods, the study shows how different radial loads affect both structural safety and lifetime of alloy wheels for optimizing real-world driving performance. Anelectric vehicle alloy wheel of Skoda was used for simulation. This study on finite element modeling presents the stress distribution of an alloy wheel. Radial fatigue test implemented using radial experiment suitable for specimen by following industrial standards. Fatigue life cycle of the wheel was measured and also to achieve material improvement.
Keywords: Electric vehicle; alloy wheels; fatigue life; heat dissipation; simulations; stress distribution